Muscle mass, quality, and strength; physical function and activity; and metabolic status in cachectic patients with head and neck cancer. (February 2023) - Ohmae, Nao; Yasui-Yamada, Sonoko; Furumoto, Taiki; Wada, Kyoko; Hayashi, Haruka; Kitao, Midori; Yamanaka, Ayaka; Kubo, Miyu; Matsuoka, Momoyo; Kamimura, Seiichiro; Shimada, Aki; Sato, Nori; et al.
Summary: Background & aims: Cancer cachexia is commonly associated with poor prognosis in patients with head and neck cancer (HNC). However, its pathophysiology and treatment are not well established. The current study aimed to assess the muscle mass/quality/strength, physical function and activity, resting energy expenditure (REE), and respiratory quotient (RQ) in cachectic patients with HNC. Methods: This prospective cross-sectional study analyzed 64 patients with HNC. Body composition was measured via direct segmental multifrequency bioelectrical impedance analysis, and muscle quality was assessed using echo intensity on ultrasonography images. Muscle strength was investigated utilizing handgrip strength and isometric knee extension force (IKEF). Physical function was evaluated using the 10-m walking speed test and the five times sit-to-stand (5-STS) test. Physical activity was examined using a wearable triaxial accelerometer. REE and RQ were measured via indirect calorimetry. These parameters were compared between the cachectic and noncachectic groups. Results: In total, 23 (36%) patients were diagnosed with cachexia. The cachectic group had a significantly lower muscle mass than the noncachectic group. Nevertheless, there was no significant difference in terms of fat between the two groups. The cachectic group had a higher quadriceps echo intensity and a lower handgrip strength and IKEF than the noncachectic group. Moreover, they had a significantly slower normal and maximum walking speed and 5-STS speed. The number of steps, total activity time, and time of activity (<3 Mets) did not significantly differ between the two groups. The cachectic group had a shorter time of activity (≥3 Mets) than the noncachectic group. Furthermore, the cachectic group had a significantly higher REE/body weight and REE/fat free mass and a significantly lower RQ than the noncachectic group. Conclusions: The cachectic group had a lower muscle mass/quality/strength and physical function and activity and a higher REE than the noncachectic group. Thus, REE and physical activity should be evaluated to determine energy requirements. The RQ was lower in the cachectic group than that in the noncachectic group, indicating changes in energy substrate. Further studies must be conducted to examine effective nutritional and exercise interventions for patients with cancer cachexia. Highlights: Parameters were compared between patients with head and neck cancer with or without cachexia. The cachectic group had lower muscle mass, quality, and strength and reduced physical function. The cachectic group had lower activity and higher REE. The RQ was lower in the cachectic group than in the noncachectic group.